Effects of Instrument-Assisted Compressive Versus Decompressive Myofascial Release in Patients with Non-Specific Low Back Pain: Non-Specific Low Back Pain - Shehzad, Sheeraz; Mughal, Samraiz; Arslan, Rana Muhammad; Farooq, Umer; Imran, Aliha; Jabeen, Misbah; Rohail, Zoya Binte; Ghaffar, Tamjeed (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2023)
Non-specific low back pain, a common condition, affects vast majority of the population worldwide and can be treated with soft tissue mobilization either with compression or decompression. Objective: To compare the effects of instrument-assisted compressive versus decompressive myofascial release on pain intensity, lumbar range of motion, and disability in non-specific low back pain. Methods: This quasi-experimental study was conducted at Laeeque Rafiq Hospital from February 2023 to April 2023. Two groups were included: one received instrument-assisted compressive myofascial release (Ergon tool), and the other received decompressive myofascial release with dry cupping. The study followed the patients for three weeks, collecting measurements of pain intensity, lumbar flexion and extension range of motion (ROM), and disability scores of low back pain. Data analysis were performed using SPSS 21.0. Results: There were a total of 44 patients. 23 patients were assigned to the compressive myofascial release technique group and 21 patients to the decompressive myofascial release group. Pain severity and disability score in the decompressive myofascial release group reduced significantly compared to the compressive myofascial release group at the end of the third week and first week respectively (p-value=0.02 and p-value=0.05 respectively). Lumbar flexion and extension ROM improved significantly in the compressive release group as compared to the decompressive release group after 1st and 2nd week respectively (p-value=0.01 and p-value=0.04 respectively). Conclusions: Decompressive myofascial release reduces low back pain and disability, while compressive myofascial release improves lumbar range of motion.